Financial inclusion as a catalyst for economic growth: evidence from selected developing countries - Nasir Khan; Md. Sharif Hassan; Mohd Faizal Yusof; Md. Aminul Islam; Maisha Marium Rahim (Cogent Social Sciences, 2024)
This study examines the connection between economic growth and financial inclusion, with a particular emphasis on Bangladesh, Malaysia, and Pakistan. This study examined data from these nations between 2004 and 2019 using panel data analysis. The findings of the fixed-effect regression showed that financial inclusion had a major and favorable impact on economic growth in each of the three countries. It was also discovered that several other factors, including inflation, population growth, and trade openness, significantly and favorably affect economic growth. According to paired Granger causality tests, the variables had a unidirectional association. The results indicate that financial inclusion contributes to economic growth in Bangladesh, Malaysia, and Pakistan; hence, governments of these nations should develop plans to increase financial inclusion.